Epoxy resin composition, prepreg and fiber-reinforced composite material

By crosslinking the epoxy resin composition with a specific composition with a polyamine curing agent and an epoxy group-free compound, the problem of insufficient elasticity and strength of the epoxy resin in the composite material is solved, and the manufacturing of high-performance composite material is realized.

JP7622437B2Active Publication Date: 2025-01-28TORAY INDUSTRIES INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020570083
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-15
Filing Date
2020-11-05
Publication Date
2025-01-28
Estimated Expiration
2040-11-05

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously increase the elasticity, strength and glass transition temperature (TG) of epoxy resins, resulting in limited application in high-performance composite materials.

Method used

An epoxy resin composition with a specific composition includes an epoxy resin, a polyamine curing agent and an epoxy group-free compound of a specific molecular weight and boiling point. By controlling its molar ratio and dissolution parameters, a highly elastic and high-strength crosslinking structure is formed.

Benefits of technology

The high elasticity, strength and glass transition temperature of the epoxy resin composition in the composite material are achieved, and is suitable for the manufacturing of high-performance composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622437000001
    Figure 0007622437000001
  • Figure 0007622437000002
    Figure 0007622437000002
  • Figure 0007622437000003
    Figure 0007622437000003
Patent Text Reader

Abstract

The present invention addresses the problem of providing an epoxy resin composition which is suitable for use in applications including prepregs and fiber-reinforced composite materials and which comes to have a high Tg and excellent modulus and strength. This epoxy resin composition comprises the following constituent elements [A]-[C] and satisfies the following requirements (1) and (2). [A]: An epoxy resin [B]: A polyamine hardener [C]: One or more compounds which each have a boiling point of 130°C or higher and a molecular weight m of 50-250 and have no epoxy group in the molecule and substantially no ability to harden epoxy resins (1): At least some of the constituent element [C] has such a Hansen solubility parameter that the sum of the polarity component and the hydrogen-bonding component is 10.0 or less. (2): The ratio of the number of moles C of the constituent element [C] satisfying the requirement (1) to the number of moles E of epoxy groups of the constituent element [A], C / E, is 0.01-0.20.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an epoxy resin composition that is suitably used for fiber-reinforced composite materials for aerospace applications, general industrial applications, sports applications, and the like, and to a prepreg and a fiber-reinforced composite material each using the epoxy resin composition. [Background technology]

[0002] Fiber-reinforced composite materials using carbon fibers, aramid fibers, or the like as reinforcing fibers are widely used, taking advantage of their high specific strength and specific elastic modulus, in structural materials for aircraft and automobiles, etc., sports materials such as tennis rackets, golf shafts, fishing rods, bicycles, and housings, general industrial applications, etc. As the resin composition used in these fiber-reinforced composite materials, thermosetting resins are mainly used from the viewpoints of heat resistance and productivity, and among them, epoxy resins are preferably used from the viewpoint of mechanical properties such as adhesion to reinforcing fibers.

[0003] In recent years, in order to apply fiber-reinforced composite materials to applications requiring further weight reduction, various physical properties need to be improved. Therefore, in order to improve various mechanical properties of fiber-reinforced composite materials, there is a demand for improvements in the elastic modulus, elongation, strength, and Tg of epoxy resins used as matrix resins. However, epoxy resin cured products with high elastic modulus and Tg are generally brittle and tend to have low elongation and strength. For this reason, it has been a technical challenge to simultaneously improve high elastic modulus, Tg, elongation, and strength.

[0004] Various studies have been conducted to improve this problem. For example, a method has been studied to improve elasticity and strength by combining an epoxy resin having a specific structure with a nanofiller (Patent Document 1). In addition, a method has been studied to improve resin strength by blending an additive to reduce the amount of dicyandiamide used as a curing agent that remains undissolved and causes defects (Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-95675 A [Patent Document 2] International Publication No. 2019 / 181402 Summary of the Invention [Problem to be solved by the invention]

[0006] Even when the technology of Patent Document 1 is used, the mechanical properties of the obtained cured resin and fiber-reinforced composite material are not sufficient, and further improvement in the mechanical properties is required. In addition, when the technology of Patent Document 2 is used, the effect of improving the resin strength is obtained, but no consideration is given to improving the elastic modulus or Tg, and a technology that can improve all of the elastic modulus, Tg, and strength is required.

[0007] Therefore, an object of the present invention is to provide an epoxy resin composition which has a high Tg, an excellent elastic modulus and a high strength and can be suitably used for prepregs and fiber-reinforced composite materials. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention employs the following means. That is, the epoxy resin composition of the present invention is an epoxy resin composition that contains the following components [A] to [C] and satisfies the following conditions (1) and (2). [A]: Epoxy resin [B]: Polyamine hardener [C]: A compound having a boiling point of 130° C. or higher and a molecular weight m of 50 to 250, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. (1): At least a portion of the component [C] satisfies the requirement that the sum of the polar component and the hydrogen bonding component in the Hansen solubility parameter is 10.0 or less. (2): The ratio C / E of the number of moles E of the epoxy groups in the component [A] to the number of moles C of the component [C] satisfying the above condition (1) is 0.01 or more and 0.20 or less.

[0009] The present invention also relates to a prepreg comprising the epoxy resin composition of the present invention and reinforcing fibers.

[0010] The present invention also relates to a fiber-reinforced composite material comprising a cured product of the epoxy resin composition of the present invention and reinforcing fibers. Effect of the Invention

[0011] According to the present invention, an epoxy resin composition having a high Tg and excellent elastic modulus and strength can be obtained, which can be suitably used for prepregs and fiber-reinforced composite materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. In the present invention, the term "not less than" means that the value is equal to or greater than the indicated value. The term "not more than" means that the value is equal to or smaller than the indicated value.

[0013] The resin composition of the present invention contains the components [A] to [C] as essential components. In the present invention, the term "component" refers to a compound contained in the composition.

[0014] The component [A] in the present invention is an epoxy resin. As the epoxy resin of the component [A], one containing two or more epoxy groups in one molecule is preferable because it can increase the glass transition temperature of the cured product obtained by heat curing the resin composition and improve the heat resistance. Also, an epoxy resin containing one epoxy group in one molecule may be blended. These epoxy resins may be used alone or in appropriate blends.

[0015] Examples of the epoxy resin of the component [A] include epoxy resins of diaminodiphenylmethane type, diaminodiphenylsulfone type, aminophenol type, bisphenol type, metaxylenediamine type, 1,3-bisaminomethylcyclohexane type, isocyanurate type, hydantoin type, phenol novolac type, orthocresol novolac type, trishydroxyphenylmethane type, and tetraphenylolethane type, etc. Among these, epoxy resins of diaminodiphenylmethane type, aminophenol type, and bisphenol type are particularly preferably used because of their well-balanced physical properties.

[0016] Commercially available diaminodiphenylmethane epoxy resins include ELM434 (manufactured by Sumitomo Chemical Co., Ltd.), Araldite (registered trademark) MY720 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY721 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY9512 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY9663 (manufactured by Huntsman Advanced Materials Co., Ltd.), Epotohto (registered trademark) YH-434 (manufactured by Tohto Kasei Co., Ltd.), and jER (registered trademark) 630 (manufactured by Mitsubishi Chemical Corporation).

[0017] Commercially available diaminodiphenylsulfone type epoxy resins include TG3DAS (manufactured by Mitsui Fine Chemicals, Inc.).

[0018] Commercially available aminophenol type epoxy resins include ELM120 (manufactured by Sumitomo Chemical Co., Ltd.), ELM100 (manufactured by Sumitomo Chemical Co., Ltd.), jER (registered trademark) 630 (manufactured by Mitsubishi Chemical Corporation), Araldite (registered trademark) MY0500 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY0510 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY0600 (manufactured by Huntsman Advanced Materials Co., Ltd.), and Araldite (registered trademark) MY0610 (manufactured by Huntsman Advanced Materials Co., Ltd.).

[0019] Commercially available bisphenol A type epoxy resins include "EPON (registered trademark)" 825 (manufactured by Mitsubishi Chemical Corporation), "Epicron (registered trademark)" 850 (manufactured by DIC Corporation), "Epototo (registered trademark)" YD-128 (manufactured by Tohto Kasei Co., Ltd.), and DER-331 and DER-332 (all manufactured by The Dow Chemical Company).

[0020] Commercially available bisphenol F type epoxy resins include "Araldite (registered trademark)" GY282 (manufactured by Huntsman Advanced Materials), "jER (registered trademark)" 806, "jER (registered trademark)" 807, "jER (registered trademark)" 1750 (all manufactured by Mitsubishi Chemical Corporation), "Epicron (registered trademark)" 830 (manufactured by DIC Corporation), and "Epotohto (registered trademark)" YD-170 (manufactured by Tohto Kasei Co., Ltd.).

[0021] The epoxy resin composition of the present invention may also contain epoxy compounds other than those mentioned above.

[0022] The component [B] in the present invention is a polyamine curing agent. The polyamine curing agent has a plurality of amino groups (including an embodiment having two amino groups) capable of reacting with an epoxy group, and functions as a curing agent.

[0023] Examples of polyamine curing agents include aliphatic polyamines and aromatic polyamines. These polyamine curing agents may be used alone or in combination. Aromatic polyamines, especially aromatic diamines, are excellent as curing agents in that they can impart high mechanical properties and heat resistance to the epoxy resin cured product.

[0024] Classified as aromatic polyamines include diethyltoluenediamines such as 2,2'-diethyldiaminodiphenylmethane, 2,4-diethyl-6-methyl-m-phenylenediamine, 4,6-diethyl-2-methyl-m-phenylenediamine, and 4,6-diethyl-m-phenylenediamine, 4,4'-methylenebis(N-methylaniline), 4,4'-methylenebis(N-ethylaniline), 4,4'-methylenebis(N-sec-butylaniline), N,N'-di-sec-butyl-p-phenylenediamine, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylsulfone, 4,4'-diaminodiphenylsulfone, and 3,3'-diisopropyl-4,4'-diaminodiphenylmethane. , 3,3'-di-t-butyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 3,3'-diisopropyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetra-t-butyl-4,4'-diaminodiphenylmethane, and the like. Of these, 3,3'-diaminodiphenyl sulfone and 4,4'-diaminodiphenyl sulfone are preferably used because the resulting cured product has excellent mechanical properties.

[0025] Commercially available aromatic polyamines include Seikacure S (manufactured by Wakayama Seika Kogyo Co., Ltd.), MDA-220 (manufactured by Mitsui Chemicals, Inc.), "jER Cure (registered trademark)" W (manufactured by Mitsubishi Chemical Corporation), and 3,3'-DAS (manufactured by Mitsui Chemicals, Inc.), "Lonzacure (registered trademark)" M-DEA (manufactured by Lonza Corporation), "Lonzacure (registered trademark)" M-DIPA (manufactured by Lonza Corporation), "Lonzacure (registered trademark)" M-MIPA (manufactured by Lonza Corporation), and "Lonzacure (registered trademark)" DETDA 80 (manufactured by Lonza Corporation).

[0026] The amount of polyamine curing agent in the present invention is preferably 0.50 or more and 1.30 or less, more preferably 0.70 or more and 1.20 or less, and even more preferably 0.80 or more and 1.10 or less, in terms of the ratio H / E between the number of moles of epoxy groups in the component [A] and the number of moles of active hydrogen in the polyamine curing agent. By setting H / E in this range, a crosslinked structure can be appropriately formed by the reaction between the epoxy resin and the polyamine curing agent, and a resin cured product excellent in strength and elongation can be obtained. In addition, by setting H / E to 0.80 or more and 1.10 or less, the component [C] described later is easily retained in the crosslinked structure, and the effect of improving the elastic modulus, strength, and elongation can be obtained.

[0027] The component [C] is a compound having a boiling point of 130°C or higher and a molecular weight m of 50 to 250, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. Here, compounds such as amines and phenols capable of addition reaction with epoxy resins, acid anhydrides capable of copolymerizing with epoxy resins, imidazoles capable of acting as self-polymerization initiators for epoxy resins, aromatic urea compounds, and tertiary amine compounds are compounds capable of hardening epoxy resins, but do not fall under the category of compounds not capable of hardening epoxy resins.

[0028] The component [C] is not incorporated into the crosslinked structure formed by the reaction of the epoxy resin and the polyamine, but exists in the voids, and is maintained in this state even after curing. This increases the elastic modulus of the resulting epoxy resin cured product. Surprisingly, the inventors have found that by blending the component [C], an epoxy resin cured product having not only a high elastic modulus but also high elongation and high strength can be obtained. The reason for this is unclear, but the inventors believe it to be as follows. The component [C] does not have an epoxy group in the molecule and does not substantially have the ability to cure the epoxy resin, so it does not react with the epoxy resin or polyamine that form the crosslinked structure. Therefore, the component [C] is not bound by a covalent bond to the crosslinked structure formed by the reaction of the epoxy resin and the polyamine, and is appropriately held in the voids of the crosslinked structure, so that the voids in the cured product can be effectively filled, and the elastic modulus of the cured product is increased. In addition, the inventors believe that when strain is applied to the cured product, component [C] can move freely within the crosslinked structure, thereby mitigating the strain energy leading to fracture, thereby increasing the elongation and strength of the cured product.

[0029] In addition, by making the boiling point of the component [C] 130°C or higher, more preferably 180°C or higher, it is possible to suppress the volatilization of the component [C] when the epoxy resin composition is cured, and to obtain a resin cured product or a fiber-reinforced composite material having excellent mechanical properties. Furthermore, this is preferable because it can suppress the generation of voids and the deterioration of mechanical properties in the obtained fiber-reinforced composite material. In the present invention, the boiling point is a value at normal pressure (101 kPa). In addition, when the boiling point at normal pressure cannot be measured, the converted boiling point converted to 101 kPa using a boiling point conversion chart can be used.

[0030] The molecular weight m of the component [C] is 50 or more and 250 or less. By setting the molecular weight of the component [C] in this range, the component [C] is appropriately held in the voids of the crosslinked structure formed by the reaction of the epoxy resin and the polyamine, and a cured product excellent in elastic modulus, strength, and elongation is obtained. In addition, by setting the molecular weight m of the component [C] to 70 or more and 250 or less, a cured product with particularly excellent elastic modulus is obtained, and by setting it to 120 or more and 200 or less, a cured product with even more excellent elastic modulus is obtained. In addition, by setting it to 50 or more and 120 or less, a cured product with particularly excellent strength and Tg can be obtained.

[0031] It is also important that at least a part of the epoxy resin composition of the present invention, the component [C], satisfies that the sum (δP+δH) of the polar component (δP) and the hydrogen bond component (δH) in the Hansen solubility parameter (HSP) is 10.0 or less (condition (1)), and is preferably 8.0 or less, more preferably 7.0 or less, and further preferably 6.0 or less. The smaller the sum of the polar component and the hydrogen bond component in the HSP of the component [C], the more the Tg decrease of the obtained epoxy resin cured product can be suppressed.

[0032] Here, the Hansen solubility parameter (HSP) is a type of solubility parameter expressed by three components, namely, a dispersion component (δD), a polar component (δP), and a hydrogen bond component (δH), and can be expressed as a three-dimensional vector. The HSP value at 25°C can be calculated uniquely from the chemical structure of each component by using computer software Hansen Solubility Parameter in Practice (HSPiP) (http: / / www.hansen-solubility.com). In the present invention, the value at 25°C of the target compound is calculated and used by using HSPiP ver.5.0.06 (sold by Eizou Kobo Question Co., Ltd.).

[0033] When a compound of two or more components is used as the component [C], it is judged whether or not each component of the component [C] satisfies the above condition (1).

[0034] Examples of the component [C] that satisfies the above condition (1) include 1,2-dimethylbenzene, 1,3-dimethylbenzene, 1,4-dimethylbenzene, biphenyl, 1,2-diphenylbenzene, 1,3-diphenylbenzene, 1,4-diphenylbenzene, etc. These compounds may be used alone or in appropriate combination.

[0035] In the epoxy resin composition of the present invention, it is important that the ratio C / E between the number of moles E of epoxy groups in the component [A] and the number of moles C of the component [C] satisfying the condition (1) is 0.01 or more and 0.20 or less (condition (2)). By setting C / E within this range, the component [C] is appropriately held in the voids of the crosslinked structure formed by the reaction of the epoxy resin with the polyamine, and a cured product excellent in elastic modulus, strength, elongation, and Tg can be obtained. In addition, by setting the molecular weight m of the component [C] to 120 or more and 200 or less, and setting C / E to 0.01 or more and 0.20 or less, preferably 0.07 or more and 0.13 or less, a cured product having particularly excellent elastic modulus and strength can be obtained.

[0036] In the epoxy resin composition of the present invention, it is preferable that at least a part of the component [C] satisfies that the Hansen solubility parameter distance (HSP distance) L with the component [A] is 20.0 or less, more preferably 10.0 or less, and even more preferably 5.0 or less. The smaller the HSP distance L between the component [A] and the component [C], the higher the affinity between the component [A] and the component [C] and the easier it is to be homogeneously compatible, so that it is possible to suppress the components [A] and [C] from being separated when the epoxy resin composition is cured. Therefore, the component [C] is more likely to be appropriately held in the voids of the crosslinked structure, and an excellent effect of improving the elastic modulus and strength is obtained.

[0037] Here, the HSP distance is a three-dimensional vector (δ D , δ P , δ H), it is a parameter that corresponds to the distance between three-dimensional vectors whose coordinates are the three components of two different substances. The smaller the HSP distance L, the higher the affinity between the two substances is estimated to be. If the HSP of the first substance is δ D1 , δ P1 , δ H1 and the HSP of the second substance is δ D2 , δ P2 , δ H2 In this case, the HSP distance L can be calculated by the formula (1).

[0038]

number

[0039] In the present invention, when two epoxy resin components are mixed and used as the component [A], the HSP value of the mixed epoxy resin calculated by the following method can be used as the HSP of the component [A]. Da , δ Pa , δ Ha Epoxy resin 1 with HSP of δ Db , δ Pb , δ Hb When epoxy resin 2 is mixed in a mass ratio of Wa:Wb, the HSP (δ Dm , δ Pm , δ Hm ) is the value calculated using formula (2).

[0040]

number

[0041] Furthermore, when three or more epoxy resin components are mixed and used as component [A], the HSP value of the mixed epoxy resin, expressed as the sum of the three-dimensional vectors of the HSPs of each component, can be used as the HSP of component [A].

[0042] When two or more compounds are used as the component [C], the HSP distance L between each compound of the component [C] and the component [A] is calculated. It is preferable that the HSP distance L between each compound of the component [C] and the component [A] is 20.0 or less.

[0043] In the epoxy resin composition of the present invention, the ratio of the number of moles E of the epoxy group of the component [A] to the number of moles of the component [C] satisfying both the condition (1) and the condition related to the HSP distance L with the component [A] ((the number of moles of the component [C] satisfying both the condition (1) and the condition related to the HSP distance L with the component [A]) / E) is preferably 0.01 or more and 0.20 or less. By setting it within such a range, the component [C] is appropriately held in the voids of the crosslinked structure formed by the reaction of the epoxy resin with the aromatic diamine, and a cured product excellent in elastic modulus, strength, and elongation is obtained. In addition, it is preferable that the molecular weight m of the component [C] is 120 or more and 200 or less, and (the number of moles of the component [C] satisfying both the condition (1) and the condition related to the HSP distance L with the component [A]) / E is 0.01 or more and 0.20 or less, more preferably 0.07 or more and 0.13 or less, thereby obtaining a cured product having particularly excellent elastic modulus and strength.

[0044] The epoxy resin composition of the present invention has excellent elastic modulus, strength, and elongation, and is suitable for use as a matrix resin for fiber-reinforced composite materials. Methods for obtaining fiber-reinforced composite materials include methods in which the resin composition is impregnated into reinforcing fibers in a molding process, such as the hand lay-up method, the RTM method, the filament winding method, and the pultrusion molding method, and methods in which a prepreg in which the resin composition has been previously impregnated into reinforcing fibers is molded by the autoclave method or the press molding method. Among these, it is preferable to prepare a prepreg made of the epoxy resin composition and reinforcing fibers in advance, since the fiber arrangement and the resin ratio can be precisely controlled and the properties of the composite material can be maximized.

[0045] The reinforcing fibers used in the prepreg and fiber-reinforced composite material of the present invention are preferably carbon fiber, graphite fiber, aramid fiber, glass fiber, etc., with carbon fiber being particularly preferred. There are no limitations on the form or arrangement of the reinforcing fibers, and for example, fiber structures such as long fibers aligned in one direction, single tow, woven fabric, knit, and braided cord are used. As the reinforcing fibers, two or more types of carbon fibers, glass fibers, aramid fibers, boron fibers, PBO fibers, high-strength polyethylene fibers, alumina fibers, silicon carbide fibers, etc. may be used in combination.

[0046] Specific examples of carbon fibers include acrylic, pitch and rayon carbon fibers, with acrylic carbon fibers having particularly high tensile strength being preferably used.

[0047] The carbon fiber can be in the form of twisted yarn, untwisted yarn, non-twisted yarn, etc., but in the case of twisted yarn, the filaments that make up the carbon fiber are not oriented parallel to one another, which can cause a decrease in the mechanical properties of the resulting carbon fiber reinforced composite material. Therefore, untwisted yarn or non-twisted yarn, which provide a good balance between the formability and strength properties of the carbon fiber reinforced composite material, are preferably used.

[0048] The tensile modulus of the carbon fiber is preferably 200 GPa or more and 440 GPa or less. The tensile modulus of the carbon fiber is affected by the crystallinity of the graphite structure constituting the carbon fiber, and the higher the crystallinity, the higher the modulus. This range is preferable because the rigidity and strength of the carbon fiber reinforced composite material are all balanced at a high level. The more preferable modulus is 230 GPa or more and 400 GPa or less, and even more preferably 260 GPa or more and 370 GPa or less. Here, the tensile modulus of the carbon fiber is a value measured according to JIS R7608 (2008).

[0049] The prepreg of the present invention can be produced by various known methods. For example, the prepreg can be produced by a hot melt method in which a resin composition is heated to reduce its viscosity without using an organic solvent and then impregnated into reinforcing fibers.

[0050] In the hot melt method, a resin composition whose viscosity has been reduced by heating can be directly impregnated into the reinforcing fibers, or a release paper sheet with a resin film can be first prepared by coating the resin composition on release paper or the like, and then a resin film can be placed on the reinforcing fiber side from both sides or one side of the reinforcing fibers, and the reinforcing fibers can be impregnated with the resin composition by heating and pressurizing.

[0051] The content of reinforcing fibers in the prepreg is preferably 30% by mass or more and 90% by mass or less. By making it 30% by mass or more, more preferably 35% by mass or more, and even more preferably 65% ​​by mass or more, it is easy to obtain the advantages of a fiber-reinforced composite material having excellent specific strength and specific elastic modulus. In addition, when molding the fiber-reinforced composite material, it is possible to prevent the amount of heat generated during curing from becoming too high. On the other hand, by making it 90% by mass or less, more preferably 85% by mass or less, it is possible to prevent the generation of voids in the composite material due to poor resin impregnation. In addition, it is possible to maintain the tackiness of the prepreg.

[0052] The fiber-reinforced composite material of the present invention can be produced, for example, by laminating the above-mentioned prepregs of the present invention in a predetermined shape and curing the resin by applying pressure and heat. Methods for applying heat and pressure include press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, etc.

[0053] The fiber-reinforced composite material of the present invention can be widely used in aerospace applications, general industrial applications, and sports applications. More specifically, in general industrial applications, it is preferably used in structures such as automobiles, ships, and railway vehicles. In sports applications, it is preferably used in golf shafts, fishing rods, and tennis and badminton rackets. EXAMPLES

[0054] The present invention will be described in detail below with reference to examples. However, the scope of the present invention is not limited to these examples. The unit "parts" in the composition ratio means parts by mass unless otherwise noted. Furthermore, the measurements of various characteristics (physical properties) were performed in an environment with a temperature of 23°C and a relative humidity of 50% unless otherwise noted.

[0055] <Materials used in the Examples and Comparative Examples> (1) Component [A]: Epoxy resin "Araldite (registered trademark)" MY0600 (aminophenol type epoxy resin, epoxy equivalent: 118g / eq, number of epoxy groups: 3, δD: 19.1, δP: 8.3, δH: 7.5, manufactured by Huntsman Advanced Materials, Inc.) "jER (registered trademark)" 825 (bisphenol A type epoxy resin, epoxy equivalent: 170 g / eq, number of epoxy groups: 2, δD: 18.9, δP: 6.6, δH: 5.3, manufactured by Mitsubishi Chemical Corporation) Glycidol (molecular weight: 74 g / mol, epoxy equivalent: 74 g / eq, number of epoxy groups: 1, boiling point: 167°C, δD: 17.7, δP: 11.5, δH: 17.0, manufactured by Tokyo Chemical Industry Co., Ltd.).

[0056] (2) Component [B]: Aromatic diamine 3,3'-DAS (3,3'-diaminodiphenyl sulfone, active hydrogen equivalent: 62g / eq, number of active hydrogens: 4, manufactured by Mitsui Chemicals Fine Co., Ltd.).

[0057] (3) Component [C]: a compound having a boiling point of 130° C. or higher and a molecular weight m of 50 to 250, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. 1,4-Dimethylbenzene (boiling point: 139°C, molecular weight m: 106, δD: 18.2, δP: 3.1, δH: 3.4, manufactured by Tokyo Chemical Industry Co., Ltd.) ·Biphenyl (boiling point: 256℃, molecular weight m: 154, δD: 19.0, δP: 2.1, δH: 3.2, manufactured by Tokyo Chemical Industry Co., Ltd.) 1,4-Diphenylbenzene (boiling point: 389°C, molecular weight m: 230, δD: 19.5, δP: 2.3, δH: 3.1, manufactured by Tokyo Chemical Industry Co., Ltd.). 1,2-Tetradecanediol (boiling point: 331°C, molecular weight m: 230, δD: 16.3, δP: 4.6, δH: 11.7, manufactured by Tokyo Chemical Industry Co., Ltd.) (4) Other compounds Methylcyclopentane (boiling point: 72°C, molecular weight m: 84, δD: 16.1, δP: 0.1, δH: 0.1, manufactured by Tokyo Chemical Industry Co., Ltd.) p-Quaterphenyl (boiling point: 428°C, molecular weight m: 306, δD: 19.8, δP: 2.4, δH: 3.0, manufactured by Tokyo Chemical Industry Co., Ltd.) N,N'-diphenyl-4-methoxybenzamide (boiling point: 468°C, molecular weight m: 303, δD: 20.1, δP: 7.0, δH: 4.6, manufactured by Tokyo Chemical Industry Co., Ltd.).

[0058] <Various evaluation methods> The epoxy resin composition of each example was measured using the following measurement methods.

[0059] (1) Three-point bending test of cured resin The uncured resin composition was degassed in a vacuum, and then heated from 30°C at a rate of 1.7°C / min in a mold set to a thickness of 2 mm using a 2 mm Teflon (registered trademark) spacer, held at 125°C for 5 hours, and then heated at a rate of 1.7°C / min to cure at 225°C for 2 hours to obtain a 2 mm thick plate-shaped cured resin. A test piece 10 mm wide and 60 mm long was cut out from this cured resin, and tested on an Instron universal testing machine (manufactured by Instron Corp.) with a span of 32 mm, a crosshead speed of 2.5 mm / min, and the number of samples n=6 according to JIS K7171 (1994). The average values ​​of the elastic modulus, strength, and elongation were taken as the elastic modulus, strength, and elongation of the cured resin, respectively.

[0060] (2) Measurement of glass transition temperature of cured resin A test piece with a width of 12.7 mm and a length of 55 mm was cut out from the resin cured plate prepared in the same manner as in (1) above, and the glass transition temperature was determined by the DMA method according to SACMA SRM18R-94. The glass transition temperature was determined as the intersection temperature between the tangent in the glassy state and the tangent in the transition state in the storage modulus G' curve. Here, the measurement was performed at a heating rate of 5°C / min and a frequency of 1 Hz.

[0061] <Example 1> (Preparation of resin composition) A resin composition was prepared by the following method.

[0062] In a kneading device, 100 parts of "Araldite (registered trademark)" MY0600 as the component [A] shown in Table 1 was charged and heated to a target temperature of 55 to 65°C while kneading, and 53 parts of 3,3'-DAS as the component [B] was added and stirred for 30 minutes. Thereafter, 9 parts of 1,4-dimethylbenzene was added as the component [C] and stirred for an additional 10 minutes to obtain a resin composition.

[0063] In this case, the ratio H / E of the number of moles H of active hydrogen in the component [B] to the number of moles E of epoxy groups in the component [A] was 1.00, the ratio C / E of the number of moles C of the component [C] to the number of moles E of epoxy groups in the component [A] was 0.10, and the Hansen solubility parameter distance L between the component [A] and the component [C] was 6.9.

[0064] The resin composition thus obtained was subjected to three-point bending measurement of the cured resin product, which showed a modulus of elasticity of 5.2 GPa, strength of 191 MPa, and elongation of 4.7%. The glass transition temperature of the cured resin product was measured, and Tg was 196° C. Compared with Comparative Example 1 (not containing component [C]) described later, excellent modulus of elasticity, strength, and elongation were obtained.

[0065] <Examples 2 to 6> The components [A], [B] and [C] were mixed in the same manner as in Example 1 above according to the mixing ratios in Table 1 to obtain a resin composition.

[0066] The results of various measurements in the examples are shown in Table 1. Even when the formulation of the resin composition was changed as in Examples 2 to 6, excellent elastic modulus, strength, elongation and Tg of the cured resin were obtained.

[0067] <Comparative Examples 1 to 7> The components [A] and [B] (and [C] or a substitute thereof) were blended in the same manner as in Example 1 above according to the blending ratios in Table 2 to obtain a resin composition.

[0068] No equivalent to the component [C] was blended in Comparative Example 1. Comparing Comparative Example 1 with Example 1, it is clear that the incorporation of the component [C] improved the elastic modulus, strength, and elongation of the cured resin material, and in particular the strength and elongation were dramatically improved.

[0069] Comparative Example 2 also does not contain anything equivalent to the component [C]. Comparing Comparative Example 2 with Example 2, it is clear that the incorporation of the component [C] dramatically improves the elastic modulus and strength of the cured resin material.

[0070] In Comparative Example 3, methylcyclopentane was blended in place of the component [C]. Methylcyclopentane does not satisfy the condition that the boiling point of the component [C] is 130°C or higher. Comparing Comparative Example 3 with Example 2, it is found that blending the component [C] that satisfies the requirement of a boiling point of 130°C or higher improves the elastic modulus and strength of the obtained cured resin.

[0071] In Comparative Example 4, p-quaterphenyl was used instead of the component [C]. p-quaterphenyl does not satisfy the condition that the molecular weight m of the component [C] is 50 or more and 250 or less. Comparing Comparative Example 4 with Example 2, it is found that the elastic modulus, strength, and Tg of the obtained cured resin are improved by making the component [C] satisfy the above condition.

[0072] In Comparative Example 5, 1,2-tetradecanediol was used instead of the component [C]. 1,2-tetradecanediol does not satisfy the condition that the sum of the polar component and the hydrogen bond component in the Hansen solubility parameter is 10.0 or less. Comparing Comparative Example 5 with Example 2, it can be seen that when the sum of the polar component and the hydrogen bond component in the Hansen solubility parameter of the component [C] is 10.0 or less, the decrease in Tg of the obtained resin cured product is suppressed and the elastic modulus and strength are improved.

[0073] In Comparative Example 6, the ratio C / E of the number of moles E of epoxy groups in the component [A] to the number of moles C of the component [C] does not satisfy the condition that it is 0.01 or more and 0.20 or less. Comparing Comparative Example 6 with Example 2, it is found that by satisfying the above condition, the decrease in Tg of the obtained cured resin product is suppressed and the elastic modulus and elongation are improved.

[0074] In Comparative Example 7, N,N'-diphenyl-4-methoxybenzamide was used instead of the component [C]. N,N'-diphenyl-4-methoxybenzamide does not satisfy the condition that the molecular weight m of the component [C] is 50 or more and 250 or less, and further does not satisfy the condition that the sum of the polar component and the hydrogen bond component in the Hansen solubility parameter is 10.0 or less. Comparing Comparative Example 7 with Example 1, it can be seen that by satisfying the above conditions, the decrease in Tg of the obtained resin cured product is suppressed, and the elastic modulus, strength, and elongation are improved.

[0075] [Table 1]

[0076] [Table 2]

Claims

1. An epoxy resin composition comprising the following components [A] to [C] and satisfying the following conditions (1) to (2): [A]: Epoxy resin [B]: Polyamine curing agent [C]: A compound having a boiling point of 130° C. or higher and a molecular weight m of 50 to 250, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. (1): At least a part of the component [C] satisfies the requirement that the sum of the polar component and the hydrogen bond component in the Hansen solubility parameter is 10.0 or less. (2): The ratio C / E of the number of moles E of the epoxy groups in the component [A] to the number of moles C of the component [C] satisfying the above condition (1) is 0.01 or more and 0.20 or less.

2. 2. The epoxy resin composition according to claim 1, wherein component [B] is an aromatic diamine.

3. A prepreg comprising the epoxy resin composition according to claim 1 or 2 and reinforcing fibers.

4. A fiber-reinforced composite material comprising a cured product of the epoxy resin composition according to claim 1 or 2 and reinforcing fibers.

Citation Information

Patent Citations

  • Low-density sound absorption and insulation polymer composite and preparation method thereof

    CN103554845A

  • Insulation-layer mold-pressed structural member for extra-high-voltage direct-current power transmission and transformation and preparation method thereof

    CN104987664A

  • Easily-recoverable carbon fiber composite material based on spiral cyclic acetal epoxy resin

    CN109385043A

  • Epoxy resin composition

    JP2002020459A

  • Epoxy resin composition for composite material, fiber-reinforced composite material, and methods for producing the same

    JP2014227473A